The power of e-recruitment and employer branding on Indonesian millennials’ intention to apply for a job - Wijaya, Cindy Natalia; Mustika, Martina Dwi; Bulut, Sefa; Bukhori, Baidi (Frontiers in Psychology, 2023)
Companies need reliable employees to support their business. As e-grocery businesses in Indonesia continue to grow during the pandemic, various strategies are required to attract millennials. This study aims to prove the influence of employer branding, e-recruitment, and post-pandemic employee value proposition (radical flexibility, deeper connection, personal growth, and holistic well-being) in encouraging millennials to apply for jobs at e-grocery companies after the pandemic. Few e-grocery companies in Indonesia use employer branding and e-recruitment; this study attempts to combine these two variables to see the effect of their interaction on influencing greater millennial intentions. Using the latest experimental method, which is the experimental vignette method, we conducted three studies with a total of 619 millennial participants, who were recruited using the convenience sampling technique. All participants received a set of job advertisements as a stimulus. The results showed that e-recruitment could not significantly predict the millennials’ intentions when applying for jobs in e-grocery companies. Companies in Indonesia may need to analyze millennials’ familiarity with e-recruitment platforms, especially on company websites. However, employer branding successfully predicted millennials’ intention to apply for a job in e-grocery companies, which was not affected by the length of their work experience. Employer branding serves as a means of building job seekers’ trust through personal promotions. With this trust, job seekers are more motivated to apply to the company. When e-recruitment and employer branding were analyzed simultaneously, there were significant interactive effects on millennials’ intentions. Employer branding acted as a socialization medium to introduce e-recruitment and vice versa. E-recruitment served as a form of branding that could shape the perceptions and experiences of millennial job seekers. Lastly, the employee value proposition significantly predicted millennials’ intentions, where holistic well-being was the most sought-after value. It can support employees’ well-being and encourage them to make valuable propositions that will make e-grocery companies excel in Indonesian labor market.